Keragaman Jenis Fitoplankton Di Perairan Waduk Mulur Kabupaten Sukoharjo Provinsi Jawa Tengah - Ariska Rahmadani, Zulfa, Efri Roziaty, S. Si., M. Si (2017)
In the use of excessive reservoir will surely destructive reservoir waters mulur empowerment as aquaculture in karamba , paddy fields on the edge of reservoirs and fishing grounds which are then will affect daily necessities phytoplankton .It was using the quantitative explorative research method by surveying technique. For the sampling process were a station A (karamba), station B (fishing), and station C (rice field irigation). The identification phytoplankton found in mulur resevoir consist of 29 genus of 6 a major division that is chlorophyta ( 13 the genus , 14 species ) , bacillariophya ( 9 the genus , 12 species ) , cryptophya ( 1 the genus , 1 species ) , euglenophyta ( 2 the genus , 4 species ) , the cyanophyta ( 4 the genus , 4 species ) .Index diversity in sation A was -3,21405 , B station -3,15334 and on station C is -3,13323. It show that index phytoplankton diversity in the station a , station station b and c show H'<1, value H'<1 Showed that speciesdiversity in a transek is a little or low and water quality in the badly polluted. Keywords : Diversity, Mulur Reservoir, phytoplankton, Chlorophyta.